Implementation of QRIS as an Effort to Digitize the Payment System at MSME Grocery Stores in the Serang Baru Housing Complex Block D - Cindy Aurelia; Anidah Anidah; Na'ilah azalia efendi; Nabila friska syafira; Muhammad kosim (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid development of digital technology requires business actors, particularly micro, small, and medium enterprises (MSMEs), to adapt in order to improve service quality and transaction systems. Bunda Bila Grocery Store, located in the Serang Baru Housing Complex Block D, Bekasi Regency, West Java, represents an MSME that previously relied primarily on cash-based transactions. This study aims to examine the implementation of Quick Response Code Indonesian Standard (QRIS) as an effort to digitize the payment system and enhance business efficiency and competitiveness. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and implemented through observation, socialization, and mentoring stages. The findings indicate that QRIS implementation facilitated faster, more practical, and more secure transactions. QRIS also supported more structured financial record management and encouraged greater consumer interest in cashless payments. Although challenges related to limited digital literacy and internet connectivity were identified, the implementation generally produced positive outcomes in terms of service quality, operational efficiency, and business image. The findings suggest that QRIS serves as an effective instrument for supporting the digital transformation of MSMEs and strengthening their adaptability within the digital economy.